Phonological Alternations in The Speech of A Sevenyear-Old Indonesian Child with Delayed Speech - Taruli Elbina Tambunan (2012)
Children show many individual differences in phonological development, and the age at which a child masters all sounds may vary from three to five years old. But, when there is a ‘special needs’ childwho is undergoing delayed speech then it makes their acquisition of speech is often affected. A delayed speech child needs some more time to acquire language. Concerning to their language deficits and cognitive dysfunction, the writer is interested in making the study of phonological alternations in the speech of seven- year- old child with delayed speech. The speech of a child with delayed speech was analysed by using three types of phonological alternations: (a) Phonetically conditioned alternations (b) Phonetically & morphologically conditioned alternations, (c) Phonetically & morphologically& lexically conditioned alternations. The alternation is determined based on analysis on phonological processes based by Ingram’s theory. In collecting data, the writer recorded the speech of the child directly twice in a week as long as a month. Then, the writer analysed the data by using twelve classifications of phonological processes proposed by Ingram (1976). In this study, the writer found phonetically conditioned alternations, phonological alternations types one, in the child’s speech production. In addition, the writer also found totally eighteen phonological processes in the child’s speech. The writer concluded that a delayed speech child usually replaces those “difficult” phonemes with “easy” ones, which is produced by involving frontier parts of vocal tracts. Besides, a seven- year-old child with mental retardation was able to acquire consonants and vowels but not all words could be pronounced well.